TARIAN LEGO-LEGO PADA MASYARAKAT KAMPUNG TAKPALA KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Delita Rosalina Mauweni; Cindy Sintikhe Dollu; Bendelina Marta Malailo; Bendelina Alomau, Daud Bentro Maukallang, Halena Muna Bekata, Petrus Mau Tellu Dony (Adisam Publisher, 2025)
This study aims to examine Lego-Lego Dance in Takpala Village, North Alor District, Alor Regency. The methods used in this study are qualitative research, ethnographic approach, and data collection techniques are carried out in two ways, namely field observations and interviews with Mr Anselmus Yetimau with research results showing that the Takpalah Village Community has a symbolic meaning in the lego-lego dance movement, namely the circular movement in the lego-lego circle contains the meaning of togetherness, unity, and interconnected harmony. The movement of embracing the shoulders or waist in a lego-lego circle signifies unity in binding the bonds of brotherhood between villagers without regard to their status, gender, ethnicity, nationality, religion, or economic status, but rather supporting each other, working together, and a high spirit of mutual cooperation. The stomping of feet in the Lego-Lego dance has a symbolic meaning that illustrates strength, decisiveness, and high spirits.